2017
DOI: 10.1136/jisakos-2016-000069
|View full text |Cite
|
Sign up to set email alerts
|

Double-row rotator cuff repair yields improved tendon structural integrity, but no difference in clinical outcomes compared with single-row and triple-row repair: a systematic review

Abstract: ImportanceTechniques for arthroscopic rotator cuff repair are rapidly evolving. Single-row (SR) and double-row (DR) repair techniques have been well described, but recent studies have suggested the biomechanical superiority of transosseous-equivalent (TOE) DR repairs and triple-row (TR) repairs. However, there is conflicting literature regarding the clinical superiority of one technique over the other.ObjectiveTo systematically review the best available evidence for arthroscopic repair of rotator cuff tears us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…42 Similarly, a 2017 systematic review by Rush et al reported double-row repairs to have improved structural integrity of the tendon at short term follow up and a lower re-tear rate compared to single-row repairs (19.3% vs 30.3%, P ¼ 0.001), although there was no significant difference in clinical outcomes among single-row, double-row, and triple-row techniques (P ¼ 0.57). 43…”
Section: Treatment Optionsmentioning
confidence: 99%
“…42 Similarly, a 2017 systematic review by Rush et al reported double-row repairs to have improved structural integrity of the tendon at short term follow up and a lower re-tear rate compared to single-row repairs (19.3% vs 30.3%, P ¼ 0.001), although there was no significant difference in clinical outcomes among single-row, double-row, and triple-row techniques (P ¼ 0.57). 43…”
Section: Treatment Optionsmentioning
confidence: 99%